(3QSGdI LHd GdSeGbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce Ld PcQg hTcQJ bGFe GdMb CeQg ef GdYHO GdebJfi GdfGUM def SeY hGHUQ Edi LejY Cgd GdMb HGdLHd GdXGgQ s
(3BNQgG (B:s
(3abO fUMJce ceG jLH Ydi GdOYGA GdCHQGQ dENhGfge GdehMOjf GdCWgGQ hGdMeO ddg GdefRg YeG jYHQ HGdHUGFQ hGdCacGQ hGdTcQ dhdjg LGeY GdNdb JeJ GdQSGdI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B96s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds